IMPLEMENTATION OF PROBLEM BASED-LEARNING TO IMPROVE CRITICAL THINKING: A SYSTEMATIC LITERATURE REVIEW - Imaliyah, Lala; Andini, Oktilya; Yarohma, Dita; Hadriana (International Journal of Educational Best Practices, 2025)
Problem-Based Learning (PBL) has emerged as a crucial pedagogical approach for fostering students' critical and creative thinking skills. However, its implementation often faces challenges, such as limited resources, insufficient teacher training, and the complexity of designing meaningful problem scenarios. This study employed a Systematic Literature Review (SLR) guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to examine the application of PBL in enhancing students' critical thinking skills. An initial search yielded 342 articles, which were screened through title and abstract review, followed by full-text assessment based on predefined inclusion and exclusion criteria. After a rigorous selection process, 9 articles that met the criteria were finally analyzed in detail. The review revealed that the majority of research on PBL and critical thinking was conducted in Indonesian high school contexts. Findings consistently indicated that PBL significantly improves students' critical thinking, creative thinking, and engagement in learning activities. Studies demonstrated that when PBL is effectively integrated, students exhibit stronger analytical abilities, enhanced problem-solving skills, and increased active participation. These findings underscore the importance of integrating PBL as a core teaching methodology, especially in preparing students to meet the complex demands of a globalized and interconnected world. Despite implementation challenges, PBL offers significant potential to reshape traditional education and foster future-ready learners equipped with essential higher-order thinking skills encourage motivation and achieve optimal learning outcomes.